2017
DOI: 10.3390/e19070360
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Knowledge from the Geometric Shape of Social Network Data Using Topological Data Analysis

Abstract: Topological data analysis is a noble approach to extract meaningful information from high-dimensional data and is robust to noise. It is based on topology, which aims to study the geometric shape of data. In order to apply topological data analysis, an algorithm called mapper is adopted. The output from mapper is a simplicial complex that represents a set of connected clusters of data points. In this paper, we explore the feasibility of topological data analysis for mining social network data by addressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In addition, their study investigates the feasibility of topological data analysis for social media mining. In addition, their study showed that the shape of data can produce meaningful information [37]. This approach can be useful in analysing visual images in the media, but, as mentioned in the Introduction, our study concerned more about text as a unit of analysis.…”
Section: Graph Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their study investigates the feasibility of topological data analysis for social media mining. In addition, their study showed that the shape of data can produce meaningful information [37]. This approach can be useful in analysing visual images in the media, but, as mentioned in the Introduction, our study concerned more about text as a unit of analysis.…”
Section: Graph Theorymentioning
confidence: 99%
“…To formulate the theoretical framework, research problem and its further consequences, this study suggests the algorithm in Figure 6. most recent study conducted topological data analysis to analyse social media to predict the popularity of images in the data [37]. In addition, their study investigates the feasibility of topological data analysis for social media mining.…”
Section: Algorithm Of Theoretical Frameworkmentioning
confidence: 99%
“…They reported a monotonic increase in the ratio of popularity over the cluster. In their extended study [18] they formulated the problem statement as predicting images' popularity and reported that TDA outperforms conventional clustering algorithms such as k-means and hierarchical clustering.…”
Section: Related Workmentioning
confidence: 99%
“…Many practical complex networks, covering different fields such as communication networks and social networks [ 8 , 9 ], all undertake the objective of information transmission. Especially for communication networks, information is the most fundamental element.…”
Section: Introductionmentioning
confidence: 99%